DYNAMICS OF LEARNING IN THE TIME OF THE COVID-19 PANDEMIC - Robbi Asri; Firman; Riska Ahmad (Yayasan Citra Dharma Cindekia, 2021)
This article discusses the dynamics of learning during the Covid-19 pandemic, even though learning is one of the important things to educate the nation's life, learning is also an important system in education, learning is held as a space for interaction to build relationships between teachers and students to develop cognitive potential, psychomotor and affective. This must be supported by the dynamics of learning that runs effectively and an internal learning atmosphere that makes students interested in learning. And at this time with the Covid-19 outbreak, learning is done online and of course online learning has both positive and negative impacts. Reality shows that the dynamics of learning in Indonesia are currently disrupted by the Covid-19 outbreak which has an impact, including; 1) schools are transferred to homes by conducting online learning; 2) there is a transformation of technology-based learning media through the use of WhatsApp Group, Zoom, Google Classroom, WebEx, Youtube, and various other platforms 3) adjustment of learning methods; and 4) demands for collaboration between parents of students at home as a substitute for teachers to control children's learning. The method used is a literature review with a critical analysis of the research being conducted on a specific topic